ISLAM DAN PLURALITAS AGAMA DI INDONESIA (Analisis Sosiologi Agama tentang Potensi Konflik dan Integrasi Sosial) - Hasbullah Hasbullah (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2010)
Confession to religion pluralism in a social community promise placing forward of principle of inclusive - a principle majoring accomodation and non conflict - among them. Because, basically the each religion have various claim of truth of which wish to be upheld to continue, while heterogeneous proven existing society reality culturally and is religion. Tradition differ opinion among people, if managed better will yield something that very useful. With different idea tradition, we becoming not easy to feel most real correct by self. At different idea tradition which finish of a dialogued, there is a nuance each other criticizing of each weakness utilize improve it later on day. Governmental and Indonesia society have to will esteem and execute principle of pluralism religious and latitudinarian. Its problem, confession and freedom of diversity represent very potency good to awakening this country from tyranny a group of rampant corruption and people. Freedom principle, equation, and social justice must be upheld is abysmal of faction partitions, religion, and religious understanding.